Material Performance Tests of the Polymer-Cement Thin Spray-On Liner - Qizheng Dong; Lianjun Chen; Weimin Cheng; Zhaoxia Liu; Xiangfei Cui; Guoming Liu; Zhiwei Shi; Zhenjiao Sun; Yaqing Zhang (Geofluids)
Compared to conventional shotcrete, thin spray-on liner (TSL) has several advantages, including high efficiency, good adhesion, and low dust content. In order to study the underlying mechanism of polymers on thin spray-on liner materials, three polymers were tested in this study. They were mixed into the shotcrete materials to conduct viscosity, pulling, flexural strength, and compression tests. The correlations between the viscosity of the materials and their other mechanical properties were analyzed. The optimal mixing ratio obtained by the tests was at a polymer–cement ratio of 15%. The material had better mechanical properties overall when modified with a vinyl acetate-ethylene (VAE) copolymer emulsion. When a VAE emulsion was used to modify cement mortar, the results showed that the VAE modified mortar had the best viscosity performance of any of the tested emulsions at the same polymer–cement ratio. Because of the adhesion of the modified mortar on a marble wall, when the viscosity was 2,300–5,800 mPa·s, the slurry was evenly distributed and did not sag on the wall surface. The VAE emulsion was affected by its own viscosity, and the pull-out strength was also enhanced as the viscosity increased. As the viscosity of the VAE emulsion increased, its flexural strength initially increased and then decreased, whereas its compressive strength decreased linearly. This study provides a theoretical basis for the development and application of thin shotcrete materials.